2018
DOI: 10.1504/ijbic.2018.094223
|View full text |Cite
|
Sign up to set email alerts
|

An elitist-flower pollination-based strategy for constructing sequence and sequence-less t-way test suite

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The CAs are well studied in the literature ( 7), examples for one-test-at-a-time approach involve: Automatic Efficient Test Generator (AETG) (8), IBM's Intelligent Test Case Handler (ITCH) (9), Jenny (10), simulated annealing (SA) (8), genetic algorithm (GA) (9), ant colony algorithm (ACA) (10), Hill climbing (HC) (11), GTWAY (12), particle swarm optimization (PSO) (13), harmony search (HS) (14), cuckoo search (CS) (15), high level hyper-heuristic (HHH) ( 16), adaptive teaching learning-based optimization (ALTBO) (17), flower pollination algorithm (FPA) (18), elitist flower pollination algorithm (eFPA) (1). Examples for one-parameter-at-a-time involve: Input Parameter Order-Generalized (IPOG) (4, 5), the modified IPOG (MIPOG), IPOD, Forbes' IPOG (IPOG-F) (6), and OPAT-HS (19).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAs are well studied in the literature ( 7), examples for one-test-at-a-time approach involve: Automatic Efficient Test Generator (AETG) (8), IBM's Intelligent Test Case Handler (ITCH) (9), Jenny (10), simulated annealing (SA) (8), genetic algorithm (GA) (9), ant colony algorithm (ACA) (10), Hill climbing (HC) (11), GTWAY (12), particle swarm optimization (PSO) (13), harmony search (HS) (14), cuckoo search (CS) (15), high level hyper-heuristic (HHH) ( 16), adaptive teaching learning-based optimization (ALTBO) (17), flower pollination algorithm (FPA) (18), elitist flower pollination algorithm (eFPA) (1). Examples for one-parameter-at-a-time involve: Input Parameter Order-Generalized (IPOG) (4, 5), the modified IPOG (MIPOG), IPOD, Forbes' IPOG (IPOG-F) (6), and OPAT-HS (19).…”
Section: Related Workmentioning
confidence: 99%
“…Some of these strategies are based on algebraic algorithms in which the test size is near minimal (2,3). Nevertheless, search based computational strategies are also considered as competitive strategies and can produce minimal test suite for some configurations (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…. , CA k )) represents N × p MCA of strength t containing vectors of CA 1 to CA k , and a subset of the k columns each of strength > t [7,8]. Also, practically, not all the inputs are interacting and having an impact on each other.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Variable strength CA (VSCA) is introduced to cater for this issue. A VSCAfalse(N;t;k,v,false(CnormalA1,...,CnormalAkfalse)false) represents N×p MCA of strength t containing vectors of CnormalA1 to CnormalAk, and a subset of the k columns each of strength >t [7, 8]. Also, practically, not all the inputs are interacting and having an impact on each other.…”
Section: Basic Concepts and Literaturementioning
confidence: 99%
“…These strategies can be either deterministic or non-deterministic , Cohen, et al, 1997;Lei, et al, 2008. Some of the combinatorial strategies adopted metaheuristics algorithms for searching the test space , Ahmed, et al 2012;Alsewari and Zamli, 2012;Hazli, et al, 2012;Rahman, et al, 2014;Yang, et al, 2014;Ahmed, et al, 2015;Prasad, et al, 2015;Zamli, et al, 2016;Rabbi, 2017;Zamli, et al, 2017;Nasser, et al, 2018. Due to the NP-Hard problem, Colburn makes a dedicated website to record minimal upper bound for CA ,Colbourn, 2019. Earlier works also reported that the number of tuples increased significantly when increased the number of parameters and/or the strength of coverage and/or the parameter-values.…”
Section: Research Trends In Combinatorial Testingmentioning
confidence: 99%